2009
DOI: 10.3810/pgm.2009.01.1969
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Quality of Sleep among Hypertensive Patients in a Semi-Urban Nigerian Community: A Prospective Study

Abstract: Poor sleep is common in hypertensive patients and may be associated with lower health-related quality of life. Large-scale, prospective, longitudinal studies on quality of sleep in hypertensive patients are needed to confirm the high prevalence of impaired quality of sleep in this population and to examine the association between severity of hypertension and quality of sleep while controlling for potential confounding variables. We hypothesize that severity of hypertension directly influences quality of sleep,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
4
27
1
1
Order By: Relevance
“…16,17 Nevertheless, the existing body of evidence is not entirely consistent, as insignificant associations between poor sleep and blood pressure (BP) have been found across different study regions, such as the American continent 18,19 and Africa. 20 This observation indicates that the relationship between sleep quality and hypertension may vary across continents. In addition, several studies have revealed that patients with hypertension have higher global PSQI scores (indicative of poorer sleep quality) than patients with normotension.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…16,17 Nevertheless, the existing body of evidence is not entirely consistent, as insignificant associations between poor sleep and blood pressure (BP) have been found across different study regions, such as the American continent 18,19 and Africa. 20 This observation indicates that the relationship between sleep quality and hypertension may vary across continents. In addition, several studies have revealed that patients with hypertension have higher global PSQI scores (indicative of poorer sleep quality) than patients with normotension.…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep has also been associated with significantly higher levels of systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) in Asian and European studies . Nevertheless, the existing body of evidence is not entirely consistent, as insignificant associations between poor sleep and blood pressure (BP) have been found across different study regions, such as the American continent and Africa . This observation indicates that the relationship between sleep quality and hypertension may vary across continents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparently high prevalence in this study may be attributed to lower health-related quality of life, low socio-economic status and concomitant poor medical conditions, and to snoring which is common among hypertensive subjects in South Western Nigeria [26]. In addition, it could also results from Obstructive sleep apnea (OSA) was high in Nigeria [27].…”
Section: Discussionmentioning
confidence: 83%